Integrating process and factor understanding of environmental innovation by water utilities - Spiller, Marc; McIntosh, Brian S.; Seaton, Roger A. F.; Jeffrey, Paul (Springer, 2015)
Innovations in technology and organisations are central to enabling the water sector to adapt to major environmental changes such as climate change, land degradation or drinking water pollution. While there are literatures on innovation as a process and on the factors that influence it, there is little research that integrates these. Development of such an integrated understanding of innovation is central to understanding how policy makers and organisations can stimulate and direct environmental innovation. In the research reported here a framework is developed that enables such an integrated analysis of innovation process and factors. From research interviews and the literature twenty factors were identified that affect the five stages of the environmental innovation process in English and Welsh water utilities. The environmental innovations investigated are measures taken by water utilities to reduce or prevent pollution in drinking water catchments rather than technical measures to treat water. These Source Control Interventions are similar to other environmental innovations, such as ecosystem and species conservation, in that they emphasise the mix of technology, management and engagement with multiple actors. Results show that in water utilities direct performance regulation and regulation that raises awareness of a ‘performance’ gap as a ‘problem’ can stimulate innovation, but only under particular organisational, natural physical and regulatory conditions. The integrated framework also suggests that while flexible or framework legislation (e.g. Water Framework Directive) does not stimulate innovation in itself, it has shaped the option spaces and characteristics of innovations selected towards source control instead of technical end-of-pipe solutions.
Keywords: innovation process; factors; catchment management; water utilities